Optimal search from multiple distributions with infinite horizon - Jean-Michel Benkert; Igor Letina; Georg Nöldeke (University of Zurich, Department of Economics, 2017)
With infinite horizon, optimal rules for sequential search from a known distribution feature a constant reservation value that is independent of whether recall of past options is possible. We extend this result to the the case when there are multiple distributions to choose from: it is optimal to sample from the same distribution in every period and to continue searching until a constant reservation value is reached.
Keywords: D83; 330; Optimal Search; Search Intensity; Infinite Horizon; Recall